37 + 8x = 4(7 - x)
37 + 8x = 28 - 4x
37 = 28 - 12x
12x = 28 - 37 <--Here's where you went wrong:
12x = -9 <--Looks like you subtracted 12 from 28 instead
x = -9/12
x = -3/4 or -0.75
28 - 37 is -9, not -16
Otherwise you did the problem exactly right. You followed the correct steps. Just a simple subtraction error!
2006-12-31 05:14:00
·
answer #1
·
answered by Rockstar 6
·
1⤊
0⤋
Equation is: 37 + 8x = 4 (7 - x)
37 + 8 x = 28 - 4x
transposeP 8 x + 4x = -37 + 28
12 x = .9 (decimal 9)
x = .9/12 (decimal 9 divided by 12)
therefore x + - 3/4
Proof: 37 + 8 x = 4 (7 - x)
37 + (8 x.-.75) = 28 - (4 x -,75)
37 + -6 = 28 - (-3)
31 = 28 + 3 = 31 Proof
2006-12-31 09:35:55
·
answer #2
·
answered by David C 2
·
1⤊
0⤋
37+8x=4(7-x) distribute 4
37+8x=28-4x add 4x to each side
37+12x=28 subtract 37 from each side
12x=-9 divide both sides by 12
x=-3/4
You stated off fine but made a simple arithmetic error
37+8x=28-4x
37=28-4x-8x
37=28-12x
12x=28-37
***29-37=-9, not -16***
12x=-16
x=16/12=-4/3
2006-12-31 07:02:24
·
answer #3
·
answered by yupchagee 7
·
1⤊
0⤋
37 + 8x = 4(7 - x)
Distribute the 4
37 + 8x = 28 - 4x
Now get x on one side
37 - 37 + 8x + 4x = 28 - 37 - 4x + 4x
12x = -9
Now divide both sides by 12
12x / 12 = -9/12
x = - 9/12
Now reduce -9/12 by dividing both the numerator and denominator by 3, giving you - 3/4
2006-12-31 06:09:33
·
answer #4
·
answered by j 4
·
1⤊
0⤋
37+8x=28-4x
37=28-4x-8x
37=28-12x
12x=28-37 = -9 not -16
x = -9/12 = -3/4
2006-12-31 05:06:26
·
answer #5
·
answered by Mena M 3
·
2⤊
0⤋
*Use distribution on the left side >
37 + 8x = 4(7) - 4(x)
37 + 8x = 28 - 4x
First: solve for "x" and keep it on one side by itself (left) and keep other variables on the opposite side (right) > subtract 37 from both sides:
37 - 37 + 8x = 28 - 37 - 4x
8x = -9 - 4x
Second: add 4x to both sides:
8x + 4x = -9 - 4x + 4x
12x = -9
Third: divide both sides by 12:
12x/12 = -9/12
x = -3/4
2006-12-31 09:53:56
·
answer #6
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
37 +8x =28 - 4x
37 +8x+4x = 28 -4x +4x
37 + 12x = 28
37-37 +12x = 28-37
12x = -9
12x / 12= -9/12
so x = -9/12 then you find the lowest common denominator and -9/12 = -3/4
hope this helps
2006-12-31 05:30:06
·
answer #7
·
answered by Grev 4
·
1⤊
0⤋
28-37 = -9
2006-12-31 05:04:37
·
answer #8
·
answered by yljacktt 5
·
4⤊
0⤋
37+8x=4(7-x)
37+8x=28-4x
-28 -28
9+8x= -4x
-8x -8x
9= -12x
-12 /-12
9/-12=x
-3/4= x
2006-12-31 05:13:20
·
answer #9
·
answered by chris18j2002 2
·
1⤊
0⤋
28-37=-9
so the answer is
x=-9/12 = -3/4
=)
2006-12-31 05:08:26
·
answer #10
·
answered by IQ DOSON 2
·
1⤊
0⤋